A Validation Study of Transgenerational Effects of Childhood Conditions on the Third Generation Offspring's Economic and Health Outcomes Potentially Driven by Epigenetic Imprinting - Gerard J. van den Berg; Pia Pinger (Institute for the Study of Labor (IZA), 2014)
At the crossroads of economics and human biology, this paper examines the extent to which pre-puberty nutritional conditions in one generation affect productivity-related outcomes in later generations. Recent studies have found a negative association between conditions at ages 8-12 and the grandchild's over-all and cardiovascular and diabetes mortality in a single historical dataset. It has been argued that this association reflects epigenetic imprinting, which has been corroborated in animal studies. We provide an external validation by analyzing the impact of the German famine of 1916-1918 on children and grandchildren of those exposed to the famine at ages 8-12. Our findings support and extend the evidence so far. Among the third generation, males (females) tend to have higher mental health scores if their paternal grandfather (maternal grandmother) was exposed. We do not find robust effects on the probability of obtaining an upper secondary education.
Keywords: I12; J11; 330; famine; transgenerational transmission; epigenetics; mental health; education; long-run effects; nutrition; intergenerational effects; slow-growth period